Designer Drugs 2.0. Issue 2 (13th January 2017) - Huestis, MA; Tyndale, RF
Abstract : This "Designer Drugs 2.0" issue of Clinical Pharmacology & Therapeutics focuses on novel psychoactive substances, primarily cannabinoids and cathinones, and the repurposing of established psychoactive compounds (e.g., modafinil, psilocybin, lysergic acid diethylamide, and 3, 4‐methylenedioxymethamphetamine) that simultaneously offer new pharmacotherapies and pose serious health problems. Novel psychoactive substances were initially used as potent tools to investigate endogenous neurotransmitter systems; for example, synthetic cannabinoids have much higher potency than Δ9‐tetrahydrocannabinol at the cannabinoid receptors. However, they are now being used illicitly as well as being tested for their efficacy in numerous clinical indications. Likewise, previously established psychoactive drugs are being repurposed as treatments for a wide variety of indications where currently approved medications are ineffective. This set of papers examines the arising problems associated with designer drugs (e.g., adverse events, psychosis, rapid new synthesis, abuse liability testing, internet sales, scheduling) as well as the potential therapeutic promises in areas as diverse as cognition enhancement, exercise‐mimetics, epilepsy, multiple sclerosis, and posttraumatic stress disorder.